A twenty years bibliometric analysis (2002-2021) of business economics research in ASEAN - Budi Harsanto; Egi Arvian Firmansyah (Cogent Business & Management, 2023)
ASEAN is predicted to be the world's largest single market by 2030, after the US, China, and the EU. This study aims to discover research performance in all ASEAN countries, including identifying output levels, research focus, and influential authors in the region. The approach used in this study is a bibliometric analysis of publications indexed in the WoS database for the past two decades (2002-2021). Of the more than 20,000 documents analyzed, it was indicated that each ASEAN country has exclusive and non-exclusive keywords. Singapore has the highest number of citations among the other ASEAN countries.
Keywords: 650; ASEAN; bibliometric; business economics; research performance; Web of Science